First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations THE PEOPLE'S LEAGUE OF HEALTH. INCOME AND EXPENDITURE ACCOUNT, from 13th February, 1919, to 30th June, 1920 EXPENDITURE. £ s. d. s. d. By Rent of Furnished Offices 81 0 0 „ Coal and Electric Light 5 12 8 „ Caretaker 11 17 0 98 9 8 „ Salaries 234 11 11 „ National Health Insurance 8 0 „ Hire of Typewriters and Typing 8 3 4 „ Insurance 10 5 „ Telephone 11 4 10 „ Sundry Office Expenses 25 19 11 „ Stamps on Cheques 16 8 „ Press Cuttings 3 18 9 „ Advertising 1 9 0 287 2 10 „ Printing and Stationery 148 18 8 „ Postages 44 17 0 193 15 8 „ Expenses of Meetings and Propaganda 58 16 0 „ Leicester Branch Expenses 21 8 0 659 12 2 „ Balance to Balance Sheet 363 8 10 £1,023 1 0 INCOME. £ s. d. £ s. d. To DONATIONS— Founders 800 0 0 Life Fellows 10 0 0 Sundry 114 14 0 924 14 0 „ SUBSCRIPTIONS— Fellows Annual 81 12 0 Members 1 0 0 82 12 0 „ Bank Interest 15 15 0 £1,023 1 0 200/B/3/2/C693/1/71